Numerical Simulation of Deep-Sea Sediment Transport Induced by a Dredge Experiment in the Northeastern Pacific Ocean - Purkiani, Kaveh; Gillard, Benjamin; Paul, André; Haeckel, Matthias; Haalboom, Sabine; Greinert, Jens; de Stigter, Henko; Hollstein, Martina; Baeye, Matthias; Vink, Annemiek; Thomsen, Laurenz; Schulz, Michael (Frontiers in Marine Science, 2021)
Predictability of the dispersion of sediment plumes induced by potential deep-sea mining activities is still very limited due to operational limitations on in-situ observations required for a thorough validation and calibration of numerical models. Here we report on a plume dispersion experiment carried out in the German license area for the exploration of polymetallic nodules in the northeastern tropical Pacific Ocean in 4,200 m water depth. The dispersion of a sediment plume induced by a small-scale dredge experiment in April 2019 was investigated numerically by employing a sediment transport module coupled to a high-resolution hydrodynamic regional ocean model. Various aspects including sediment characteristics and ocean hydrodynamics were examined to obtain the best statistical agreement between sensor-based observations and model results. Results show that the model is capable of reproducing suspended sediment concentration and redeposition patterns observed during the dredge experiment. Due to a strong southward current during the dredging, the model predicts no sediment deposition and plume dispersion north of the dredging tracks. The sediment redeposition thickness reaches up to 9 mm directly next to the dredging tracks and 0.07 mm in about 320 m away from the dredging center. The model results suggest that seabed topography and variable sediment release heights above the seafloor cause significant changes especially for the low sedimentation pattern in the far-field area. Near-bottom mixing is expected to strongly influence vertical transport of suspended sediment.